Jaroslav Miller: Uzavřená společnost a její nepřátelé. Město středovýchodní Evropy (1500–1700).: Lidové Noviny: Praha 2006, 463 pp. In English The Closed Society and its Enemies. Towns of Central Eastern Europe (1500–1700) announced for March 2008 by Ashgate. - Klusáková, Luďa (Lidé města, 2008)
A review of the book by Jaroslav Miller.